Peran Wakaf Sebagai Instrumen Pembiayaan UMKM Pasca Pandemi Covid 19 - Alwi, Mochamad Amaludhin; Mubarok, Zaky (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
This study aims to determine the role of waqf in developing MSMEs through financing schemes. This research uses a qualitative method with a literature study approach. The literature study was conducted by reviewing and examining various literature and policies related to the concept and role of waqf as an instrument for financing MSMEs after the Covid-19 pandemic. The results of this study show that waqf and MSMEs have a very close relationship in an effort to realize community welfare. The role of waqf as an alternative source of financing for MSMEs is carried out through the distribution pattern of waqf benefits as well as in the form of cash waqf.